Improved pretreatments applied to the sugarcane bagasse and release of lignin and hemicellulose from the cellulose-enriched fractions by sulfuric acid hydrolysis - Miranda, Ismael [UNESP]; Masiero, Maria O. [UNESP]; Zamai, Thamyres [UNESP]; Capela, Marisa Veiga [UNESP]; Laluce, Cecília [UNESP] (Wiley, 2014)
BACKGROUND A number of pretreatments have been reported in the literature aiming to improve yields with increases in degree of digestibility of the cellulose-enriched fractions, in reducing the process time recalcitrance and costs of a variety of chemicals reagents and physical processes were used. Nevertheless, none of them was considered completely satisfactory. RESULTS Modifications and simplifications were made in pretreatments to increase gravimetric yields and to decrease the losses of mass. The highest gravimetric yields and the lowest loss of mass were obtained for cellulose-enriched fractions resulting from microwave pretreatments. Loss of mass during treatments with sulfuric acid were due to dehydration of sugars forming furan aldehydes. Cellulose-enriched fractions PT6 and PT7 are certainly more easily by commercial enzymes as indicated by loss of mass. CONCLUSIONS Pretreatments with sulfuric acid resulted in less recalcitrant cellulose-enriched fractions that will give enzymatic hydrolysates containing less inhibitors of yeast cells. FeCl3 greatly modified the yields of total reducing sugars, glucose, furan aldehydes and phenolic compounds released from the cellulose-enriched fractions by sulfuric acid. However, the co-catalytic effect on the sulfuric acid hydrolysis was dependent on the pretreatment used and acid concentration.
Keywords: Sugarcane biomass; Total reducing sugars; Xylose; Cellulose-enriched fractions; Phenolic compounds; Furan aldehydes